Implementasi Model Pembelajaran REPICPRO (Resume, Picture, Problem Based Learning) Mata Pelajaran IPS Kelas VII SMP Pada Materi Kelangkaan Dan Kebutuhan Manusia - Prastyaningtyas, Efa Wahyu; Wulansari, Widi (Efektor, 2020)
The aim of this quasi experimental study is to find out how the implementation of REPICPRO modelon social sciences subject of seventh grade students at Junior High School to scarcity and humanneeds materials. One group pre-test pos-ttest design was used in this research. The data analyzestechnique used Paired t-test. The result showed that there was a difference score between pre-testand post-test with t- score of 5,461 and significance of 0,0001. The average of pre- test score was66 and post- test score was 77,33. Thus, the result of the study showed that student learningoutcomes was increased, so that the implemetation of the REPICPRO method had a positive andsignificant effect on the learning outcomes of seventh grade students to scarcity and human needsmaterials.